Inclusive Education Importance and Problems for Students Social Integration - Derzhavina, Veronika V. (2021)
The article relevance. Modern concepts of education development, recognition of the uniqueness and self-worth of human individuality have led to the search for ways to socialize individuals with disabilities, to the development of new pedagogical strategies aimed at developing ideas of independent life for this category of the population. The research purpose is to study the features and identify ways to improve the quality of inclusive education. Research methods: as a research method, we used a questionnaire survey as a method of collecting primary information, which allows us to identify various aspects related to the problems of formation and perception of inclusive education by participants in the educational process. Research results: the article describes the peculiarity of the current stage of inclusive education development, analyzes the social mechanisms for improving the quality of inclusive education. The novelty and originality of the research lies in the fact that for the first time the correspondence of the existing model of inclusive education to the needs of a significant part of the educational process subjects was investigated. It is shown that, from the point of view of educational services’ consumers, a significant obstacle to improving the quality of inclusive education is the orientation of the education system on results, and not the educational process. It is revealed that the main functions of an inclusive school are educational, career-oriented, educational, and integrative. It is shown that relationships with teachers are a significant factor of psychological stress in inclusive classes. It is found that inclusive classes are sufficiently distanced from interaction with the local community. It is shown that teachers lack the skills of teamwork and confident behavior of the teacher in the presence of another adult in the classroom. It is revealed that the inclusive school is currently characterized by a high level of internal unity, but is not focused on external relations with the local community.  It is shown that parents, unlike students, note the creation of an accessible environment only for certain categories of children with disabilities (including children with musculoskeletal disorders), but not for children with sensory disorders (vision and hearing). Practical significance: the data Obtained in this work can be used in psychological research, pedagogical Sciences, age psychology, as well as for further theoretical development of this issue